Measurement scale for online flow conditions: A new approach based on shopping applications - Borba, Eduardo Henrique de; Tezza, Rafael; Meseguer-Artola, Antoni (Journal of Telecommunications and the Digital Economy, 2025)
The concept of online flow refers to users' immersive and holistic experience while browsing the internet. Although this cognitive state has been widely studied, it depends on specific conditions often analysed from the user's perspective, such as the balance between demands and abilities, the clarity of objectives, and the nature of feedback received. This study aims to explore online flow conditions specifically in shopping applications by proposing a measurement scale, an area that has received limited attention in the literature. To achieve this, an in-depth literature review was conducted, followed by methodological procedures for scale construction outlined by DeVellis (2017). This process involved defining relevant dimensions, formulating specific items, and applying them to a sample of 200 shopping applications from Brazil and Spain, along with rigorous validation and confirmation of the scale's internal consistency. The results reveal the creation of an innovative and statistically validated scale, demonstrating its effectiveness as a tool for measuring online flow conditions in virtual environments. Applying this scale provides valuable insights for developers, enabling the creation of digital environments that foster flow and enhance user engagement.